2018
DOI: 10.1161/strokeaha.118.022631
|View full text |Cite|
|
Sign up to set email alerts
|

Ceria Nanoparticles Synthesized With Aminocaproic Acid for the Treatment of Subarachnoid Hemorrhage

Abstract: Background and Purpose— Despite early aneurysm repair and aggressive management for complications, subarachnoid hemorrhage (SAH) results in at least 25% mortality rate and 50% persistent neurological deficit. We investigated whether ceria nanoparticles which have potent antioxidative activities can protect against subarachnoid hemorrhage via attenuating fatal brain injuries. Methods— Uniform, 3 nm, water-dispersed ceria nanoparticles were prepared from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…CeNPs have both SOD mimetic (eradicating superoxide anions and hydroxyl radicals) and catalase mimetic (eradicating hydrogen peroxide), which enable it to eradicate ROS repetitively. Previous studies demonstrated that CeNPs treatment could protect against BBB disruption and neuronal death in several CNS disorders (23,37). However, whether CeNPs treatment shows similar bene ts in WMI is still contentious.…”
Section: Discussionmentioning
confidence: 99%
“…CeNPs have both SOD mimetic (eradicating superoxide anions and hydroxyl radicals) and catalase mimetic (eradicating hydrogen peroxide), which enable it to eradicate ROS repetitively. Previous studies demonstrated that CeNPs treatment could protect against BBB disruption and neuronal death in several CNS disorders (23,37). However, whether CeNPs treatment shows similar bene ts in WMI is still contentious.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been various studies conducted on NPs for application in haemorrhagic stroke. Jeong et al studied CeO 2 NPs and their ROS scavenging abilities in the context of subarachnoid haemorrhage, the most devastating type of stroke, which is known to have a flux of ROS produced in the early progression of the disease [ 170 ]. The same investigators synthesized CeO 2 NPs using aminocaproic acid as a surface modifier, and conducted a randomized trial in an animal model to determine whether free radical scavenging therapy using the synthesized NPs, reduced mortality and improved neurological outcomes.…”
Section: Nanoparticle-based Cns Theranosticsmentioning
confidence: 99%
“…The same investigators synthesized CeO 2 NPs using aminocaproic acid as a surface modifier, and conducted a randomized trial in an animal model to determine whether free radical scavenging therapy using the synthesized NPs, reduced mortality and improved neurological outcomes. They reported that the NPs displayed a strong capability to protect the brain against subarachnoid haemorrhage, via prominent and versatile ROS scavenging effects, suggesting the potential for future clinical applications, warranting further preclinical testing such as profiling of pharmacokinetics and toxicity effects [ 170 ]. You et al investigated loading NPs with astaxanthin (ATX), a carotenoid with strong antioxidant and inflammatory properties [ 171 ].…”
Section: Nanoparticle-based Cns Theranosticsmentioning
confidence: 99%
“…102 In a rat hemorrhagic stroke model, IV injection of CeO 2 nanoparticles had reduced neuronal death, immune cell infiltration and cerebral edema. 103 These do not however exemplify DDS technology. Therefore, in a recent study, CeO 2 nanoparticles were loaded with edaravone and conjugated with angiopep-2 and PEG.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%